1994
DOI: 10.1086/133504
|View full text |Cite
|
Sign up to set email alerts
|

The gas-phase iron abundance in Herbig-Haro objects

Abstract: ABSTRACT. The gas-phase abundance ratios Fe/S and Fe/O have been determined for the Herbig-Haro objects HH 1, HH 7, HH 11, HH 43A, and "Burnham's Nebula" (HH 255). It is the purpose of this study to decide whether a sizeable fraction of the Fe in these HH objects is still bound in dust grains or whether the observed matter has gone through sufficiently fast shock waves so that the dust grains have been essentially destroyed and most of the iron has gone back into the gas phase. We have determined the abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In this case the estimate does not depend upon assumptions of the shock characteristics (velocity, pre-shock density, magnetic field intensity) but depends on the accuracy of the determinations of the gas parameters. Beck-Winchatz et al (1994 used this method to estimate Fe and Ni gas-phase abundance in HH jets. They found that Fe is not, or only partially, depleted in HH jets, while Ni is surprisingly over-abundant.…”
Section: Observational Estimates Of Calcium Gas-phase Abundance In Stmentioning
confidence: 99%
“…In this case the estimate does not depend upon assumptions of the shock characteristics (velocity, pre-shock density, magnetic field intensity) but depends on the accuracy of the determinations of the gas parameters. Beck-Winchatz et al (1994 used this method to estimate Fe and Ni gas-phase abundance in HH jets. They found that Fe is not, or only partially, depleted in HH jets, while Ni is surprisingly over-abundant.…”
Section: Observational Estimates Of Calcium Gas-phase Abundance In Stmentioning
confidence: 99%
“…This method was first applied to HH objects by Beck-Winchatz et al (1994, using a large sample of op- Nisini et al (2002) proposed two other methods to measure the Fe gas phase abundance in young stellar jets, relying only on near-infrared lines. The first one involves the [Fe ] 1.257 µm/Paβ ratio, assuming that Paβ is emitted under case B recombination.…”
Section: Diagnostic Of Gas Phase Fe Abundancementioning
confidence: 99%
“…The method is simply an extension to the near-IR domain of that introduced by Beck-Winchatz et al (1994) in the optical range. As described above, it will yield a lower limit to the Fe/S ratio.…”
Section: Diagnostic Of Gas Phase Fe Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Refractory species such as Ca, Ni, Cr, and Fe are often locked onto dust grains, thus a strong depletion of their gas phase abundance is expected in the interstellar medium (ISM) (Savage & Sembach 1996). A few studies have investigated the gas phase abundance of Fe and Ni in HH jets (Beck-Winchatz et al 1994Mouri & Taniguchi 2000;Böhm & Matt 2001;Nisini et al 2002), and only recently the analysis has been extended to other refractory species such as Si, Ca, C, Cr, and Ti (Nisini et al 2005(Nisini et al , 2007Cabrit et al 2007;Podio et al 2006Podio et al , 2009Garcia Lopez et al 2008). These studies showed that the refractory species may be depleted by up to 90% in HH jets and molecular outflows, thus suggesting the presence of dust grains in the ejected material.…”
Section: Introductionmentioning
confidence: 99%